Cystic poorly differentiated squamous cell carcinoma of the scalp, a rare scalp tumor: Case report and literature review. (2019) - Shah, Amjad; Akram, Jaweria; Abdelaal, Abdelrahman; Alateeq, Layth; Ben-Gashir, Mohamed; Hammouda, Atalla
Highlights: Cutaneous cystic lesion have wide clinical differentials. A high index of suspicion should be maintained when any cutaneous lesion shows aggressive behavior. A prompt investigation should be carried before surgical resection, and histopathology provides a final diagnosis. We report a rare case of cystic poorly differentiated SCC of scalp operated as a sebaceous cyst. Abstract: Introduction: Cutaneous cystic lesions have broad differentials ranging from common benign entity to rare malignant lesions. Clinical evaluation of the lesion is the key to differentiation, as some rare malignant entities may simulate benign lesions. A high index of suspicion should be maintained for any aggressive behavior, which may require more thorough evaluation, including histopathology and radiographic imaging studies. We report a rare case of cystic poorly differentiated squamous cell carcinoma (CPDSCC) of the scalp. Case presentation: We report a case of a 37-year-old Filipino expatriate male who presented with a scalp swelling which had been gradually increasing in size for four months and was operated upon with a working diagnosis of sebaceous cyst. On post-op excisional biopsy, it turned out to be poorly differentiated cystic squamous cell carcinoma of the scalp. On further workup, no metastasis or other primary was found. Complete re-excision of the lesion with no evidence of residual tumor was achieved. Long-term follow-up was lost, as the patient left for his native country. Conclusion: Though cystic cutaneous lesions are very commonly encountered in clinical practice, high suspicion for malignancy should be maintained if the lesion shows any aggressive behavior. Prompt investigation should be done before surgery to determine the nature of the disease and the most effective management for the patient. Poorly differentiated cystic squamous cell carcinoma should also be considered in the differential diagnosis of cystic cutaneous lesions show aggressive behavior.